KEABSAHAN HAK JAMINAN ATAS RUMAH PADA PERJANJIAN KREDIT YANG DIKUASAI OLEH SUAMI TANPA PERSETUJUAN ISTRI - Lucy Ayuditya Indah Utama; Firdaus Firdaus; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Marriage in Islam is also called marriage, is a relationship of a sacred bondbetween a man and a woman, which means worship to Allah, to follow the sunnah of theapostle and is carried out on responsibility, sincerity and following the provisions of thelaw which is a close relationship. between a man and a woman who have fulfilled theconditions of marriage. The purpose of marriage according to Law Number 1 of 1974concerning marriage is that marriage aims to form a happy and eternal family based onBelief in the One and Only God, besides that the institution of marriage also aims toform male and female humans in a household life, live life together, ensuring themaintenance of human resources. One of the legal consequences of marriage is not onlydirected at the husband and wife, but also regarding the assets owned by the husbandand wife. Indonesian marriage law stipulates that assets acquired during the marriageperiod are referred to as joint assets.The purpose of this study was to determine the legitimacy of the house asjoint property between husband and wife controlled unilaterally by the husband and todetermine the distribution of shared assets equally between husband and wife. This typeof research uses the sociological method. The research location is the PekanbaruReligious Court. The data collection technique is to use primary data as the mainmaterial obtained directly in the field, namely interviews, but also supported bysecondary data, namely library materials.The results of the research on the validity of the guarantee rights over thehouse in the credit agreement that is controlled by the husband without the wife'sconsent is that there are 10 cases filed by the wife related to joint property. The reasonfor a wife to file a joint property lawsuit is because the joint property was obtained whenthey entered into a marriage and felt entitled and obliged to share the property fairly.One of the cases raised was case No. 123/Pdt.G/2019/PA.Pbr, in which case a wifemade an effort to distribute joint assets to be divided fairly, namely a plot of landcovering an area of 660M2 and building 1 unit of a 2-storey house. This effort was madeon the basis of the defendant's concern that they would lose, embezzle or transfer thejoint property.JOM Fakultas HukumUniversitas Riau Volume X Edisi 2 Juli-Desember 2023 Page 1Keywords:Joint Property-Divorce-Guarantee-Crediy